Relationship between cytokine gene polymorphisms and chronic hepatitis B virus infection - Tunçbilek, Semra (Baishideng Publishing Group Inc, 2014)
Hepatitis B virus (HBV) infection is still a public health problem worldwide, being endemic in some parts of the world. It can lead to serious liver diseases such as chronic hepatitis, cirrhosis, and hepatocellular cancer. The differences in host immune response can be one of the reasons for the various clinical presentations of HBV infection. Polymorphisms of genes encoding the proinflammatory and antiinflammatory cytokines, which are responsible for regulation of the immune response, can affect the clinical presentation of the infection. Particularly, the polymorphisms of the genes encoding cytokines such as interleukin (IL)-1, IL-6, IL-8, IL-10, IL-18, IL-28B, interferon-γ, tumor necrosis factor-α, tumor growth factor-β1, and regulatory molecules like vitamin D receptor and chemokine receptor 5 can be responsible for different clinical presentations of HBV infections. The genomic information about cytokines and other mediators can be important for determining high-risk people for developing chronic hepatitis or hepatocellular cancer and may be used to plan treatment and preventive approaches for these people. In this review, the current knowledge in the literature on the association between cytokine/regulatory molecule gene polymorphisms and clinical course of chronic HBV infection is summarized, and the clinical implementations and future prospects regarding this knowledge are discussed.